Islamic law - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
Islam is not merely a religion but is a complete way of life. It encompasses a legal, social and moral order aimed at construing the entire fabric of human life and culture in the light of values and principles revealed by Allah (s.w.t.) for the guidance of mankind. Its decrees and rules are to ensure prosperity and peace on earth and in the hereafte